Experimental Research of Reliability of Plant Stress State Detection by Laser-Induced Fluorescence Method - Yury Fedotov; Olga Bullo; Michael Belov; Viktor Gorodnichev (International Journal of Optics)
Experimental laboratory investigations of the laser-induced fluorescence spectra of watercress and lawn grass were conducted. The fluorescence spectra were excited by YAG:Nd laser emitting at 532 nm. It was established that the influence of stress caused by mechanical damage, overwatering, and soil pollution is manifested in changes of the spectra shapes. The mean values and confidence intervals for the ratio of two fluorescence maxima near 685 and 740 nm were estimated. It is presented that the fluorescence ratio could be considered a reliable characteristic of plant stress state.